Gestão de Recursos Humanos em organizações sustentáveis: análise à luz do Global Reporting Initiative e da Administração Renovada. - D´amorim, Amanda Raquel de França Filgueiras (2009)
One of the challenges to sustainability lies upon building elements of reflection and new strategies of action that rescue basic values compatible with ethics and respect to human dignity. The area of Human Resources becomes fragile upon the compatibility of its actions with the discourse of sustainability. The objective this study is to analyze Human Resources action developed in sustainable organizations at the light of Global Reporting Initiative (GRI) and of Renewed Administration. The research strategy adopted was multiple case study. For this, three were selected financial institutions banks, and that issued the report global reporting initiative (GRI) in João Pessoa/PB. For the analysis of data, we opted for technical Collective Subject Discourse proposed by Lefèvre (2005). As results, hypotheses were raised that led to conceptualization and elaboration of 20 (twenty) sustainable Human Resources actions, on line with GRI indicators, with GRH subsystems and Renewed Administration adapting to their applicability in the internal ambiance. As to the identification of the compatibility of the actions developed in RH with the indicators of sustainability (GRI) and Renewed Action the conclusion is that financial institution develop more sustainable actions or partially sustainable than properly sustainable, revealed dissonance between the discourse and the practice of management. 38 actions were distributed in the many subsystems of GRH. Amongst these, were considered able (attending completely to the references of analysis), 13 were partially sustainable (attending both the indicators of sustainability and the spects of aspects of Renewed Administration and 11 were not considered sustainable (therefore attended to no references of analysis). As to difficulties for the actions, it was observed the complexities of changes in behavior and the work timetable being strangled because of too many bank activities, there being no time for humanization. As to facilities for the conduct of actions was found the bank's commitment to sustainability. Conclude that GRI indicators for themselves do not favour the development of RH actions in the perspective of sustainability. Its association with aspects of Renewed Administration makes possible more humanitarian action in RH administration and it s strengthening with the strategies of the organization.